Effects of different carbon sources on the growth of freshwater zooplankton Moina micrura (Kurz, 1875) in biofloc system - Chittaranjan Raul; J. Praveenraj; K. Saravanan; R. Kiruba Sankar; Udipta Roy; Himanshu Sekhar Swain (Journal of Fisheries, 2026)
A 30-day study was conducted to evaluate the population growth of Moina micrura in biofloc systems using different carbon sources: jaggery, rice bran, tapioca, and coconut oil cake. Coconut oilcake and rice bran based biofloc system produced significant higher populations densities (15042±1018 and 13060±1010 individuals L–1, respectively) compared to jaggery and tapioca. The optimal production was achieved at a C:N ratio of 20:1 and a floc volume of 5 mL L–1, where peak population density was observed. M. micrura abundance showed a significant positive correlation (p ≤ 0.05) with water quality parameters pH, alkalinity, TAN-N, nitrite-N, and nitrate-N. Enhanced growth and reproductive performance in complex carbon based biofloc systems were attributed to improved nutrient availability and microbial composition. The findings demonstrate that nutrient rich biofloc systems, particularly those based on rice bran and coconut oil cake under optimized conditions, can be effectively utilized for mass culture of M. micrura, supporting improved live feed production in aquaculture.